Benefits of Flowering Plant as Refuge to Improve the Ecosystems Services by Egg Parasitoids of the Rice Brown Planthopper - Nike Grace Hanjelina Sinulingga; Y. Andi Trisyono; Edhi Martono; Buyung Hadi (Jurnal Perlindungan Tanaman Indonesia, 2019)
Outbreaks of the rice brown planthopper, Nilaparvata lugens Stal., tend to increase in 2017. There has been significant interest to reduce reliance on pesticides by manipulating habitat plant species and communities to benefit natural enemies of insect. Flowering plants as refuge can contribute in enhancing the ecosystem services. This study aimed to assess the benefit of flowering plants as refuge to improve the role of egg parasitoids of brown planthopper. We sampled three rice fields: rice field adjacent to refuge, far from refuge, and rice field with no refuge using trapping procedure. We found two genera of parasitoid in Banyumas: Oligosita and Anagrus. The parasitism in the three rice fields was 46.14, 43.05 and 42.32%, respectively, showing no differences. However, the number of parasitoids emerged from the traps placed in the rice field with refuge was higher (31.08 adults/trap) than the other two rice fields (25.67 and 20.71 adults/trap). In addition, the number of unhatched parasitoids was lower in the rice with refuge (5.9%) compared to no refuge (14.54%). These findings show that the refuge provides better environments for the parasitoid by improving the number of progeny produced which eventually could increase their role in managing N. lugens population.